Velenje, industrijsko mesto v preobrazbi - Bole, David (CAPAcities, 2020)
According to the economic indicators, Velenje has a successful, export-oriented economy with high added value per employee. But like all industrial cities in Europe, Velenje is very vulnerable. This book seeks to shed light on the aspects of Velenje's transformation in the past, present and future. The purpose of the book is to provide an overview of Velenje's developmental factors. Emphasis is placed on social, cultural, spatial, environmental, economic and other aspects of the city, as well as a critical evaluation of future development resources and their actions. The second emphasis is on the originality and specificity of certain activities and phenomena that contribute to greater creativity and resilience of Velenje. We present 16 diverse contributions to the book that critically evaluate the current and future developmental resources of Velenje and its surroundings. Articles in the book ('Velenje, an industrial city in transformation') are written by locals and experts working on the BRIGHT FUTURE project dealing with small industrial towns across Europe. Two main messages emerge from all the contributions: the importance of using our own (endogenous) development resources and a participatory way of making decisions in the future.